Hydatid cyst of the buccal mucosa: An unusual presentation - Lavanya, R. M. (Indian J Dent, 2015)
Hydatid cyst is a parasitic cyst caused by the tapeworm Echinococcus that occurs primarily in sheep grazing areas worldwide. It is a chronic disease, and the cysts can be localized in unusual anatomical and geographic locations. It is known to affect the head and neck region. Patients must undergo a thorough systemic investigation as 20–30% show multiorgan involvement. We report a case of hydatid cyst occurring in the buccal mucosa of a 45- year -old male presenting as a small asymptomatic lump and emphasize on its rarity and diagnostic issues.